Extracorporeal Shock Waves in the Treatment of Equinovarus Foot in a Duchenne Patient: A Case Report - Michele Barazzuol MD; Efthymia Lampropoulou MD; Andrea Meneghini MD; Stefano Masiero MD (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Background: Duchenne muscular dystrophy (DMD) is characterized by a progressive muscular weakness, with loss of independent ambulation. When the disease results in the complete loss of ambulation, one of the purposes of treatment during the latest phase is to prevent or reduce complications such as foot deformities.  A 20-year-old DMD patient had a complete loss of muscular strength in the inferior and superior limbs and a severe bilateral clubfoot deformity.  Active movements were not possible, while passive motion was very limited in dorsiflexion and pronation, inversion and eversion, with stronger limitation on the right foot.  First, the patient was treated with gentle manipulation and casting for two weeks, but no improvement in passive range of motion was detected.  The treatment was then modified by adding a session of focused extracorporeal shock wave therapy for five consecutive weeks. Results: After five shock wave sessions, both limbs showed a bilateral correction of the talo-metatarsal angle, respectively 26° on the right and 19° on the left foot. The most relevant improvements were estimated in the passive dorsiflexion of both ankles: with a gentle manipulation, both feet could return to the anatomical position, in such a way to allow the patient to wear his own shoes. Conclusions: There is increasing evidence that nitric oxide (NO) and vascular endothelial growth factor (VEGF) dysregulation is involved in DMD progression; on the other hand, extracorporeal shock wave therapy (ESWT) induces NO and VEGF production, thus promoting angiogenesis, and has proven effective in reducing muscular hypertone. ESWT shows a potential role in the treatment of Duchenne complications such as foot deformities, as part of a multidisciplinary rehabilitation program.